2020
DOI: 10.1101/2020.08.24.264127
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

State-dependent changes in perception and coding in the mouse somatosensory cortex

Abstract: An animal's behavioral state is reflected in the dynamics of cortical population activity and its capacity to process sensory information. To better understand the relationship between behavioral states and information processing, mice are trained to detect varying amplitudes of whisker-deflection under two-photon calcium imaging. Layer 2/3 neurons (n=1436) in the vibrissal primary somatosensory cortex are imaged across different behavioral states, defined based on detection performance (low to high-state) and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…This discrepancy could be a result of the complexity of the chosen behavioral paradigm or it could be because cortical signals are highly dynamic and context driven. More recent findings have shown that signals in primary somatosensory cortex can enhance stimulus selectivity with behavioral training 13 , fluctuate according to the behavioral state 14 , or even remap depending on downstream signals 15 . Together, these findings have opened up many questions and they motivate us to believe that neuronal signals in primary sensory areas may be highly dynamic, context or experience dependent, and part of an adaptive framework.…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy could be a result of the complexity of the chosen behavioral paradigm or it could be because cortical signals are highly dynamic and context driven. More recent findings have shown that signals in primary somatosensory cortex can enhance stimulus selectivity with behavioral training 13 , fluctuate according to the behavioral state 14 , or even remap depending on downstream signals 15 . Together, these findings have opened up many questions and they motivate us to believe that neuronal signals in primary sensory areas may be highly dynamic, context or experience dependent, and part of an adaptive framework.…”
Section: Introductionmentioning
confidence: 99%